Strategi pemitigasian bias pengukuran umum dalam evaluasi balanced scorecard dengan balikan eksplanatori - Rina Silvia; Intiyas Utami; Usil Sis Sucahyo (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2016)
This study aims to prove the existence of a common measure bias in the evaluation of Balanced Scorecard and test strategies explanatory feedback as mitigation common measure bias. Efforts mitigation impact of the proposed common measure bias in this study is to provide knowledge to the method of explanatory feedback. This research uses experimental design factorial 2x2x2 between-within subjects with 56 participants S1 Accounting students are already taking courses in management accounting. The first hypothesis testing in this research using the independent t-test, comparing the performance measurement group before getting explanatory feedback. The second hypothesis testing using a paired t-test to see performance measurement division before and after getting explanatory feedback. Results of laboratory experiments show that there is a common measure bias in the manager before receiving explanatory feedback. Explanatory feedback method is supported as a strategy mitigation common measure bias in the evaluation of BSC.